156k views
4 votes
Solve 4(x - 3) - 2(x - 1) >0.

{x I x > -5}
{x I x > 5}
{x l x < 5}
{x I x < -5}

2 Answers

1 vote

The answer is: [C]: " x > 5 " .

__________________________________________

Step-by-step explanation:

__________________________________________

Given: " 4(x − 3) − 2(x − 1) > 0 " ;

__________________________________________

Note the "distributive property of multiplication" :

__________________________________________

a(b+c) = ab + ac ;

a(b−c) = ab − ac ;

___________________________________________

So, given:

_________________________________________________

→ 4(x − 3) − 2(x − 1) > 0 ;

_________________________________________________

Let us simplify; and rewrite:

_________________________________________________

Start with:

______________________________________________________

→ -2 (x − 1) = (-2*x) − (-2 *1) = -2x − (-2) = -2x + 2 ;

______________________________________________________

Now, continue with:

→ 4(x − 3) = (4*x) − (4*3) = 4x − 12 ;

______________________________________________________

So, given the original problem:

______________________________________________________

→ 4(x − 3) − 2(x − 1) > 0 ;

______________________________________________________

Rewrite;

Replacing: "4(x − 3)" ; with: "4x − 12" ;

and replacing "− 2(x − 1)" ; with: " -2x + 2" ;

______________________________________________________

as follows: → " 4x − 12 − 2x + 2 " > 0 ;

______________________________________________________

On the "left-hand side", combine the "like terms", and simplify ;

______________________________________________________

+4x −2x = +2x ; −12 +2 = -10 ; and rewrite:

______________________________________________________

→ 2x − 10 > 0 ; Add "10" to EACH SIDE of the inequality;

______________________________________________________

→ 2x − 10 + 10 > 0 + 10 ;

______________________________________________________

to get: → 2x > 10 ;

______________________________________________________

→ Now, divide EACH SIDE of the inequality by "2";

to isolate "x" on one side of the inequality; & to "solve"/"simply" for "x" ;

_______________________________________________________

→ 2x / 2 > 10 / 2 ;

_______________________________________________________

→ x > 5 ; which is:

_______________________________________________________

→ Answer choice: [C]: " x > 5 " .

_______________________________________________________

User Nima Zarei
by
4.7k points
6 votes

Answer:

x >5

Step-by-step explanation:

4(x - 3) - 2(x - 1) >0

Distribute

4x -12 -2x +2 > 0

Combine like terms

2x -10 >0

Add 10 to each side

2x-10+10 > 10

2x>10

Divide each side by 2

2x/2 > 10/2

x >5

User SeanWM
by
5.0k points